Postman pat - Simon, Schuster (Simon & Schuster Childrens Books China, 2005)
"Postman Pat" is a beloved children's book series featuring Pat, a friendly postman in the fictional village of Greendale. Each story follows Pat as he delivers mail to the villagers and encounters various challenges along the way, often involving his black-and-white cat, Jess. Through problem-solving and teamwork, Pat ensures that everyone receives their letters and packages, highlighting themes of community, friendship, and the importance of helping others. The charming illustrations and simple, engaging plots make it a favorite for young readers.